THE IMPACT OF DIGITAL MARKETING ON MODERN BUSINESS AND ADVERTISING - Isidora Milošević; Milica Grbić; Biljana Bjelica (STED Journal)
In today’s world, alongside increased market globalization and economic regionalization, business success relies on the utilization of modern information technology. The emergence and development of the Internet and the networking of businesses and public administrations, driven by digital marketing strategies, have led to significant changes in how business systems operate and their efficiency. It has facilitated easy and fast communication, almost instant transmission of large amounts of data over long distances, simple publishing and updating of multimedia documents and their continuous global availability, digital delivery of goods and services, direct online payments, creation of virtual organizations, etc. All of these represent elements of a new form of business. Electronic commerce is a broad concept encompassing all business transactions or information exchanges conducted using information and communication technology between: businesses, businesses and their customers, or businesses and public administrations.